2020
DOI: 10.1007/978-3-658-29262-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Differences and Similarities in Motivation for Offline and Online eSports Event Consumption

Abstract: ESports is a rising phenomenon that attracts followers worldwide. Recently, big eSports events are hosted regularly as a counterpart to the "traditional" online streams. However, the differences between offline and online consumption have not been scientifically addressed. Based on the Motivation Scale for Sports Consumption (MSSC), on-site visitors and stream followers (N = 637) of a big eSports event were surveyed. By analyzing the motives for eSports consumption of these two groups, insights about users fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Many of the parents commented that they did not know or understand how the eSports games worked, but they enjoyed the socialising part of the event where they could meet other parents and socialise with them. This statement is supported by the findings of Neus (2020) and Pu et al (2022), who found that on-site attendees of eSports events were motivated by the social aspects of the events, whereas online attendees were more focused on gaining knowledge, and were interested in the intricacies of the game. Regarding knowledge of the games, this finding is further consistent with the study by Pu et al (2022), who found the need to expand one's knowledge of the eSports games as an additional motivator.…”
Section: Experience and General Rating Of Hosted Esports Eventsupporting
confidence: 52%
See 2 more Smart Citations
“…Many of the parents commented that they did not know or understand how the eSports games worked, but they enjoyed the socialising part of the event where they could meet other parents and socialise with them. This statement is supported by the findings of Neus (2020) and Pu et al (2022), who found that on-site attendees of eSports events were motivated by the social aspects of the events, whereas online attendees were more focused on gaining knowledge, and were interested in the intricacies of the game. Regarding knowledge of the games, this finding is further consistent with the study by Pu et al (2022), who found the need to expand one's knowledge of the eSports games as an additional motivator.…”
Section: Experience and General Rating Of Hosted Esports Eventsupporting
confidence: 52%
“…This is supported by Pu, Ciao and Kota (2022), who concluded that more information is currently needed on the reasons why spectators attend eSports events. Jenny et al (2018) and Neus (2020) commented that research into eSports developments will always be a fruitful area to focus on with future research projects. Pu et al (2022) highlight in their study that motivation is an important topic that should be considered when looking at sport consumer behaviour.…”
Section: Esports In South Africamentioning
confidence: 99%
See 1 more Smart Citation